Effects of Cooling Rate on the Structure of Onion Epidermal Cells - Wang Yabo; Zhu Kai; Dai Baomin; Wang Jinshan; Liu Shengchun; Xie Yanqi (Zhileng xuebao)
The dynamic variation characteristics of an onion epidermal cell structure under different cooling rates and the impact of intracellular ice crystal on the cell structure were investigated experimentally. The internal relations between pressure and volume were also discussed. The relationship between the supercooling degree, crystallization time, and cell deformation was analyzed. Additionally, the structural feature of the cells after rewarming was shown. The results indicate that the number of intracellular ice crystals formed is decreased and their size is increased with the decrease in the cooling rate, which result in more mechanical damage of cell. The average gray scale decreases by 27.5% from 2 ℃/min to 15 ℃/min and 37.5% from 2 ℃/min to 90 ℃/min. The volume of the cell decreases with increases in the internal pressure, and the cell collapses at a critical internal pressure. When the cooling rate is 2 ℃/min, the internal pressure is increased by 0.388×10-2 Pa and the volume is decreased by 2.264×10-13 m3 following the freezing–thawing process. The differences in the cooling rates have influence on the supercooling degree, crystallization time, and cell deformation. When the cooling rate is 90 ℃/min, relative volume change in the cell is 1.24% following the freezing–thawing process.